Variations in Economic Analysis Essays in Honor of Eli Schwartz - Aronson, J. Richard; Parmet, Harriet L.; Thornton, Robert; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2010)
For over fifty years, Eli Schwartz has inspired generations of students and economists through his many publications and dedication to teaching. In 2008, the Martindale Center for the Study of Private Enterprise at Lehigh University invited prominent academics and practitioners—including Nobel Prize recipients Robert Solow and Harry Markowitz, and former Chairman of the Council of Economic Advisers under Ronald Reagan, Murray Weidenbaum—to contribute pieces that reflect their approaches to issues many of which Schwartz has explored over the span of his long career. The twelve original essays cover a range of topics, including tax reform, corporate finance, fiscal policy, banking, economic growth, and globalization, and they represent a variety of methodologies, including economic theory, econometrics, and case analysis. The collection emphasizes the underlying connections among seemingly disparate facets of economic activity, and underscores the considerable influence of Schwartz on economic analysis and policy today.
My Favorite Two Corporate Finance Puzzles -- The Solvency of Federal Welfare Entitlement Programs: Social Security and Medicare -- The Corporate Sector as a Net Exporter of Funds: Additional Evidence -- Piscal Folicy 101—Economic Policy Meets Partisan Politics -- A Taxonomy of Utility Functions -- Equilibrium and Disequilibrium Growth: a Comment on a Comment -- Reputational Risk and Conflicts of Interest in Banking and Finance: The Evidence So Far -- Seeking Common Ground on Globalization -- Tax Reform Then and Now -- Joseph A. Schumpeter: Not Guilty of Plagiarism but of “Infelicities of Attribution” -- Economics and the Tanakh—the Hebrew Bible -- Muted Signals in Academe: Letters of Recommendation and Grade Inflation.
Keywords: Economic theory; Economic policy; Finance; Economics; Management science; Economic Theory/Quantitative Economics/Mathematical Methods; Economic Policy; Finance, general; Economics, general